Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1021/i200027a031
|View full text |Cite
|
Sign up to set email alerts
|

Flue gas denitrification. Selective catalytic oxidation of nitric oxide to nitrous oxide

Abstract: A study was conducted on the selective catalytic oxidation of NO in simulated flue gas. Oxidation of NO to the more reactive N2O3 and N204 (N02) would enable wet scrubbing of NO, simultaneously with S02. Fourteen catalysts were tested in a fixed-bed reactor at a space velocity of at least 1500 h~1 in the temperature range of 150 to 800 °F. The experimental results comprise a screening program for an engineering analysis rather than a full kinetic study. Eight catalysts exhibited optimum performance at 200 °F, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Transition metal oxides are cheap and also have good catalytic activity and, thus, can be appropriate catalysts for the catalytic oxidation of NO. Among the variety of transition metal catalysts, Co-based and Mn-based catalysts display the best catalytic activity for NO oxidation [11]. However, the applications of Co-based catalysts are retarded due to the toxicity of cobalt although they attract much attention [12,13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxides are cheap and also have good catalytic activity and, thus, can be appropriate catalysts for the catalytic oxidation of NO. Among the variety of transition metal catalysts, Co-based and Mn-based catalysts display the best catalytic activity for NO oxidation [11]. However, the applications of Co-based catalysts are retarded due to the toxicity of cobalt although they attract much attention [12,13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…8d , indicate that the Cu 1 Bi 1 -mBeta is very stable in the presence of SO 2 (or H 2 O and SO 2 ). It is believed that the highly crystalline zeolite framework enables the catalyst to keep good stability against H 2 O, and the highly dispersity active speicies Bi can improve the SO 2 resistance to some extent 13 , which is very important for the NH 3 -SCR of NO x in the co-existence of H 2 O and SO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…, Cu-loaded zeolite beta exhibited a good activity and hydrothermal stability in the NH 3 -SCR of NO x 11 12 . It is also reported that the introduction of Bi 2 O 3 can improve the SO 2 resistance 13 .…”
mentioning
confidence: 95%
“…15,16 Such transition metal ion species in the AlSCMS system may offer potential for specially tailored catalytic applications. 17 It is well-known that manganese oxide-loaded catalysts are useful as catalysts for various chemical reactions such as oxidation, [18][19][20] the catalytic combustion of methane 21 and volatile organic compound (VOC), 22 nitrous oxide decomposition 23 and ozone decomposition. 22 However, only a few papers have dealt with the local structural characteristics of the manganese metal ions in MCM-41 [24][25][26][27][28] and silica spheres with shell consisting of ordered mesoporous structure similar to MCM-41 hexagonal structure.…”
Section: Esr Study Of Manganese Ion Species With Solid Core/mesoporous Shell Structurementioning
confidence: 99%